Santa Fe : the railroad that built an empire - Marshall, James Leslie, 1891- (Random House, 1945)
The dream of Cyrus K. Holliday for a great railroad in the Southwest was based on the fabulous legend of the old Santa Fe Trail over which, from the time of the Conquistadores, had come the riches of New Spain : embroidered shawls, the plumes of tropical birds, laces, sugar, wine and silk. Across the plains to the Missouri they came in ever-increasing quantities and found their way to the growing land east of the Mississippi. To Santa Fe the traders in their stout ox carts carried gold, salt, copper, fur, hides, the print goods of New England mills, the gadgets of Yankee ingenuity. It was slow, but fortunes were made. The railroad that was to take over all this traffic, and more, was actually started at Topeka, Kansas on a bleak October day in 1868. Col. Holliday made a speech. Facing the incredulous but tolerant grins of his neighbors he envisioned a railroad which would join Kansas City and Santa Fe, which would go on to the Pacific Coast to meet the ships from the Orient, would tap the hidden mineral wealth of the Rockies and the traffic from Mexico, would afford shipping facilities for the vast land in between, with its cattle herds and its growing agriculture. Agriculture indeed, said the smiles of his hearers, with 75,000,000 buffaloes roaming the plains, to say nothing of the marauding bands of Indians. And how about the blizzards, and cyclones; how about mountains to cross at altitudes of seven, eight and nine thousand feet; how about the shifting sands of the deserts, the bottomless canyons, the floods, the arid waters? This is the story of how it was done, step by step, problem by problem; the Indian fighting, the depredations of buffaloes, the engineering feats, the battles for rights of way. It is a thrilling story of American adventure and empire building. In it the reader meets characters who were famous in those roaring days of the Southwest : Kit Carson, the scout; Bat Masterson, gunfighting marshal of wicked Dodge City; old Jesse Chisholm of the Chisholm Trail; Jesse James; Death Valley Scotty; the builders, Col. Holliday, A.A. Robinson, Ray Morley, Lew Kingman, William Strong; the provider, Fred Harvey. Here is an exciting story of the Indian Territory land run and the opening up of Oklahoma. Here are the good times and the bad, right down to the present, with a great transportation system dedicated to the task of war and the peacetime years ahead. It is chatty, anecdotal, breezy, but packed into its a vast amount of fascinating history, not only of a railroad, but of the whole Southwest -- Book jacket.